2024
DOI: 10.1111/hiv.13608
|View full text |Cite
|
Sign up to set email alerts
|

Impact of social determinants of health on time to antiretroviral therapy initiation and HIV viral undetectability for migrants enrolled in a multidisciplinary HIV clinic with rapid, free, and onsite B/F/TAF: ‘The ASAP study’

Anish K. Arora,
Serge Vicente,
Kim Engler
et al.

Abstract: ObjectiveMultidisciplinary care with free, rapid, and on‐site bictegravir/emtricitabine/tenofovir alafenamide (B/F/TAF) dispensation may improve health outcomes among migrants living with HIV. However, models for rapid B/F/TAF initiation are not well studied among migrants living with HIV, and an understanding of how social determinants of health (SDH) may affect HIV‐related health outcomes for migrants enrolled in such care models is limited.MethodsWithin a 96‐week pilot feasibility prospective cohort study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…[31] Another analysis from the same study in 35 migrant people with HIV identified social determinants associated with a longer timeframe to initiate B/F/TAF; none of these factors had a statistically significant impact on the time to achieve viral suppression (HIV viral load of < 50 copies/mL). [32] A retrospective chart review conducted at the University of Alberta, Edmonton, confirmed the efficacy of B/F/TAF in 50 people with previously documented primary NRTI resistance. [30] Our study provides the first prospective RWE for B/F/TAF treatment in a broad range of people with HIV across Canada.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…[31] Another analysis from the same study in 35 migrant people with HIV identified social determinants associated with a longer timeframe to initiate B/F/TAF; none of these factors had a statistically significant impact on the time to achieve viral suppression (HIV viral load of < 50 copies/mL). [32] A retrospective chart review conducted at the University of Alberta, Edmonton, confirmed the efficacy of B/F/TAF in 50 people with previously documented primary NRTI resistance. [30] Our study provides the first prospective RWE for B/F/TAF treatment in a broad range of people with HIV across Canada.…”
Section: Discussionmentioning
confidence: 85%
“…[3,8,[19][20][21] Several small real-world evidence (RWE) studies have shown the effectiveness and safety of B/F/TAF in routine clinical practice. [22][23][24][25][26][27][28][29][30][31][32] However, there is little RWE with B/F/TAF in the Canadian population. The only available evidence from Canada comes from specific population groups, such as TN migrant people in a Montreal-based multidisciplinary HIV care clinic receiving rapid cost-covered B/F/TAF initiation, [31,32] and a retrospective chart review in people with previously documented primary nucleoside reverse transcriptase inhibitor (NRTI) resistance at a single center in Alberta.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CVIS/MUHC offers multidisciplinary HIV care through a team of HIV-specialist physicians, nurses, pharmacists, a social worker, a psychologist, and a psychiatrist. In this study, all participants were initiated on bictegravir/emtricitabine/tenofovir alafenamide (B/F/TAF) rapidly (i.e., within a median of 5 days) after linkage to our clinic [ 18 ]. This manuscript presents an interim analysis of patient-reported quantitative data collected from MLWH enrolled in the ASAP study up to week 48.…”
Section: Methodsmentioning
confidence: 99%
“…As a non-probabilistic sampling method was used, no formal sample size calculation based on power considerations and effect sizes was done. However, it is important to note that pilot feasibly studies generally have a sample size of approximately 30 participants on average per intervention arm [ 18 , 19 ]. This small sample of participants does not compromise comparisons between groups of interest.…”
Section: Methodsmentioning
confidence: 99%